Resource ambidexterity through alliance portfolios and firm performance. (22nd February 2016) - Wassmer, Ulrich; Li, Sali; Madhok, Anoop
Abstract : Research summary : Partner resources can be an important alternative to internal firm resources for attaining dual and seemingly incompatible strategic objectives. We extend arguments about managing conflicting objectives typically made at the firm level to the level of a firm's alliance portfolio. Specifically, will a balance between revenue enhancement and cost reduction attained collectively through partner resources accessed via a firm's various alliances be similarly beneficial for firm performance? Additionally, how do strategic attributes of alliance portfolio configuration, specifically alliance portfolio size and partner resource scope, condition the balance‐performance relationship? Based on data from the global airline industry, we find support for the balance‐performance relationship, though such balance is less beneficial for firms in the case of access to a broader resource scope per partner . Managerial summary : Increasing revenue and reducing costs simultaneously can potentially enhance firm competitiveness. We highlight that an alliance strategy can be an important alternative to internal resources for attaining such dual strategic objectives, particularly when partner resources accessed through alliances are treated collectively as portfolios. We examine the importance of balancing product‐market extending and efficiency‐improving partner resources in the global airline industry as well as the impact of two alternate strategies for accessing resources through alliances: fewer partners with more resources per partner or more partners with fewer resources per partner. We find that resource balance at the portfolio level helps airlines improve performance. Our results also suggest that managers should be cautious of accessing too many resources through just a few partners . Copyright © 2015 John Wiley & Sons, Ltd.